Imagining spaces and places - Isomaa, Saija (Cambridge Scholars Press, 2013)
Imagining Spaces and Places seeks to produce an interdisciplinary dialogue between art history and literature studies and other fields of cultural analysis that work with the concepts of space, place and various ""scapes"", such as cityscapes, bodyscapes, mindscapes and memoryscapes, as well as the more familiar landscapes. The volume was inspired by new lines of study that underline the experiential and multidimensional aspects of spaces. We explore how art, literature or urban spaces forge "" ...